2019
DOI: 10.1111/1365-2435.13289
|View full text |Cite
|
Sign up to set email alerts
|

Experimental N and P additions alter stream macroinvertebrate community composition via taxon‐level responses to shifts in detrital resource stoichiometry

Abstract: Increases in nitrogen (N) and phosphorus (P) availability are changing animal communities, partly by altering stoichiometric imbalances between consumers and their food. Testing relationships between resource stoichiometry and consumer assemblage structure requires ecosystem‐level manipulations that have been lacking to date. We analysed patterns of macroinvertebrate community composition in five detritus‐based headwater streams subject to experimental whole‐stream N and P additions that spanned a steep gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
2
30
1
Order By: Relevance
“…However, elevated concentrations as low as 7 µg/L SRP triggered changes in resource nutrient content in our study (which was the 2‐year average SRP concentration in the target 11 µg/L SRP stream; Manning et al, 2016), indicating very little P, combined with N enrichment, can result in changes in food resource nutrient content. Increases in total organic matter flows to primary consumers were largely driven by leaf‐shredding macroinvertebrates, which exhibited the greatest response to nutrient enrichment among macroinvertebrate FFGs (Demi et al, 2019). Nutrient enrichment produced clear but modest shifts in the trophic basis of primary consumer production relative to pre‐enrichment conditions but did not alter the contribution of dominant food types (leaf detritus and fungi) to production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, elevated concentrations as low as 7 µg/L SRP triggered changes in resource nutrient content in our study (which was the 2‐year average SRP concentration in the target 11 µg/L SRP stream; Manning et al, 2016), indicating very little P, combined with N enrichment, can result in changes in food resource nutrient content. Increases in total organic matter flows to primary consumers were largely driven by leaf‐shredding macroinvertebrates, which exhibited the greatest response to nutrient enrichment among macroinvertebrate FFGs (Demi et al, 2019). Nutrient enrichment produced clear but modest shifts in the trophic basis of primary consumer production relative to pre‐enrichment conditions but did not alter the contribution of dominant food types (leaf detritus and fungi) to production.…”
Section: Discussionmentioning
confidence: 99%
“…The flow of animal prey to predators did not systematically change following nutrient enrichment and was unrelated to total flows of organic matter to primary consumers, which were dominated by leaf litter. The lack of a systematic response in flows to predatory macroinvertebrates may reflect shifts in the potential prey assemblage towards a greater prevalence of large‐bodied, predator‐resistant taxa (Davis et al, 2010a; Davis, Rosemond, Eggert, Cross, & Wallace, 2010b; Demi et al, 2019). For example, an earlier analysis of macroinvertebrate community composition in the study streams revealed that the communities shifted towards greater biomass of the common, large‐bodied shredders Pycnopsyche (Trichoptera), Tallaperla (Plecoptera) and Tipula (Diptera; Demi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eutrophic CWs, along with oligotrophic downstream environments, contribute to the maintenance of regional biodiversity [72]. Moreover, the unequal purification effect of CWs, with respect to different contaminants, can change regional stoichiometric characteristics, thus having potential impacts on regional biodiversity [73,74].…”
Section: Spatial-temporal Characteristics Of the Biodiversity Benefitmentioning
confidence: 99%
“…The C:N:P ratio of suspended particulate matters, hereafter "seston", is closely tied to biogeochemical cycles and food webs in aquatic ecosystems [1][2][3]. Since A. C. Redfield first observed that C:N:P ratios of seston in the offshore surface ocean are similar to the ratios of dissolved nutrients in the deep ocean, the classical Redfield ratio (C:N:P = 106:16:1) is routinely used to interpret and local scale.…”
Section: Introductionmentioning
confidence: 99%